Re-imagining the classroom through social justice projects: portraying students’ attitudes. - Villalobos Ulate, Nuria (2015)
This paper analyses Costa Rican college EFL learners’ attitudes and challenges when conducting social awareness projects as an initiative in an English course. The Think, Share and Act (TSA) project was initi-ated in January, 2009 with 57 students from different majors at Univer-sidad Nacional-Heredia. The students worked for about three months in planning and conducting the project in different settings. Students DUH JLYHQ WKH RSSRUWXQLW\ WR OHDUQ DERXW GLIIHUHQW JOREDO LVVXHV UHÁHFW on and discuss them, share their knowledge and experiences related to these concerns and even come up with possible action plans for social problems. The research concludes that these projects heighten interest in researching social issues, enhance social and linguistic skills and improve problem solving and leadership skills which grow levels of motivation to carry out humanitarian projects